PENGARUH CITRA MEREK, INOVASI PRODUK DAN KEPERCAYAAN MEREK TERHADAP MINAT BELI PRODUK SMARTPHONE SAMSUNG (STUDI KASUS PADA MAHASISWA UPGRIS) - Anggraini, Anisa; Indiworo, Rr. Hawik; Violinda, Qristin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The research was conducted with the aim of analyzing and explaining the effect of brand image, product innovation and brand trust on buying interest. The study was conducted on Upgris students who use Samsung Smartphones. Data were collected through observation, document analysis, and distributing questionnaires. The method of data analysis was carried out by descriptive quantitative methods using multiple regression analysis tools with the help of the SPSS program. The results showed that first, the variable brand image, product innovation and brand trust have a simultaneous effect on buying interest. Second, the brand image variable has a partial effect on the interest in the bell. Third, the product innovation variable has a partial effect on buying interest. Fourth, the variable brand trust has an effect on buying interest.